Reflecting on experiences of care: an exploratory qualitative descriptive study of the perspectives of stroke survivors, families and staff - Christopher Etherton-Beer; Rosemary Saunders; Caroline Bulsara; Laura Emery (BMJ Open)
Objective The aim of this study was to identify barriers and enablers from the perspectives of stroke survivors, carers and staff to understand the experiences of care.Design The study used a qualitative descriptive methodology and employed semistructured interview technique.Setting A metropolitan stroke rehabilitation unit in Western Australia providing rehabilitation services for inpatients and outpatients.Participants Overall, 10 participants (four staff, four stroke survivors and two primary carers) were interviewed. Transcripts were analysed using thematic analysis.Results Experiences of care focused on lack of time, urgency to regain mobility, postshock recovery, uncertainty about the future and the importance of accepting help once home. There was a degree of mismatch between staff experiences of the reality of what can be provided and the experiences and expectations of stroke survivors and families. However, the benefits of a specialised rehabilitation unit were found to contribute to a positive patient experience overall. The specialised unit demonstrated that services must optimise staff time with patients and carers in the poststroke rehabilitation journey to ensure benefits for the long-term well-being for both.Conclusion Seeking patient, family and staff experiences of care can provide valuable insights into facilitating better patient, family and staff engagement for preparation for home-based rehabilitation for stroke survivors and their caregivers. Further research with a larger sample across diverse hospital settings would provide even greater insight into strategies to best address the reality of rehabilitation care and readiness of patients when returning home to the community.